Glomerular deposition of food antigens in IgA nephropathy. - Sato, M (1988)
Recently, we reported on the importance of food antigens on the pathogenesis of an experimentally-induced model of, and some patients with, IgA nephropathy. In this paper, the glomerular deposition of food antigens (casein, lactalbumin, peanut protein, soy bean protein, rice protein, ovalbumin) was investigated by an immunofluorescence technique in 28 patients with IgA nephropathy and 32 controls (ten with lupus nephritis, three with Henoch-Schoenlein purpura nephritis and 19 with other glomerulonephritis). Glomerular IgA deposition was demonstrated in all IgA nephropathy and Henoch-Schoenlein purpura nephritis, and in four lupus nephritis. Positive findings of food antigens, observed as mesangial pattern, were obtained in eleven cases (39.3%) with casein, 21 (75.0%) with soy bean protein and one (3.6%) with rice protein in IgA nephropathy, even though no such findings were seen in the control group. Eleven of 28 patients with IgA nephropathy were positive with soy bean protein alone, nine were positive with soy bean protein + casein, one was positive with soy bean protein + casein + rice protein, and one was positive with casein alone. The deposition of food antigens was not observed in six cases only. Furthermore, no correlation was noted between the deposition of food antigens and the deposition of IgA1, IgA2 or J chain, in vitro binding of the secretory component, or histopathological grades. These results suggest that the exact meanings of glomerular deposition are unclear. Food antigens are postulated, however, as possibly participating strongly in the pathogenesis and as being localized in the glomerular mesangium as an antigen in some patients with IgA nephropathy.